Adverse Events Associated with COVID-19 Vaccination in Adolescents with Endocrinological Disorders: A Cross-Sectional Study - Erbaş, İbrahim Mert; Erbaş, İrem Ceren; Akın Kağızmanlı, Gözde; Yüksek Acinikli, Kübra; Besci, Özge; Demir, Korcan; Böber, Ece; Belet, Nurşen; Abacı, Ayhan (Journal of clinical research in pediatric endocrinology, 2023)
The aim was to evaluate the adverse events seen after Coronavirus disease-2019 (COVID-19) vaccination in pediatric patients with diagnosed endocrinological problems and to compare them with healthy controls. In this cross-sectional study, patients aged 12-18 years who attended a single department between January and May 2022 and were followed up for at least six months due to endocrine diseases, and healthy subjects in the same age group, all of whom had received a COVID-19 vaccine [BNT162b2 mRNA or inactivated vaccine] were included. Adverse events experienced after the vaccination were evaluated by questionnaire. A total of 160 subjects (85 patients, 75 healthy controls) with a median (25-75p) age of 15.5 (14.1-16.9) years were included. The frequency of adverse events was higher in those vaccinated with the mRNA vaccine compared to the inactivated one after the first dose (p=0.015). The incidence of adverse events observed after the first and second doses of both COVID-19 vaccines was similar in the patient and control groups (p=0.879 and p=0.495, respectively), with local reactions being the most common. The frequency of adverse events was similar among the patients who did or did not receive any endocrinological treatment (p>0.05). The incidence and severity of systemic reactions were similar to those in healthy subjects for both vaccine doses, regardless of the underlying diagnosis, autoimmunity state, or treatment regimen used in patients with endocrine diseases. The incidence and severity of adverse events associated with COVID-19 vaccinations in adolescents with endocrinological disorders were similar to healthy subjects, in the early post-vaccination period.